Acute Acalculous Cholecystitis Associated with Epstein–Barr Infection: A Case Report and Review of the Literature - Konstantinos Ntelis; Dimosthenis Mazarakis; Apostolos Sapountzis; Dimitra Zissi; Sophia Sparangi; Nikoletta Xidia; Dimitrios Velissaris (Case Reports in Medicine)
The most common cause of acute cholecystitis (ACC) is cholelithiasis. Acute acalculous cholecystitis (AAC) is well documented in the literature related with critical illness, but viral causes such as cytomegalovirus (CMV) and Epstein–Barr virus (EBV) have also been reported. We present a rare manifestation of EBV infection, reporting a case of a 15-year-old female suffering from acute acalulous cholecystitis, and we review the relevant literature. Clinicians should be aware of this rare complication of EBV infection and properly exclude it in young patients with cholecystitis.